Selective electron beam manufactured Ti-6Al-4V lattice structures for orthopedic implant applications: Current status and outstanding challenges. Issue 3 (June 2018) - Zhang, X.Z.; Leary, M.; Tang, H.P.; Song, T.; Qian, M.
Highlights: An in-depth critical assessment of mechanical properties of SEBM Ti-6Al-4V lattice. An exhaustive list of mechanical properties of human bone for lattice design. A comprehensive mechanical comparison of SEBM Ti-6Al-4V lattice with human bone. A clear identification of opportunities for SEBM Ti-6Al-4V lattice as bone implant. Abstract: Additively manufactured Ti-6Al-4V lattices display unique mechanical and biological properties by virtue of their engineered structure. These attributes enable the innovative design of patient-specific medical implants that (i) are conformal to the intended surgical geometry, (ii) mimic the mechanical properties of natural bone, and (iii) provide superior biological interaction to traditional implants. Selective electron beam melting (SEBM) is an established metal additive manufacturing (AM) process that has enabled the design and fabrication of a variety of novel intricate lattices for implant applications over the last 15 years. This article reviews the technical and clinical characteristics of SEBM Ti-6Al-4V lattices, including (i) the SEBM process and its capabilities, (ii) the structures of human bones with an exhaustive list of corresponding mechanical properties from literature, (iii) the mechanical properties of SEBM Ti-6Al-4V lattices of various designs and their shortcomings when compared to human bones, (iv) microstructural control of SEBM Ti-6Al-4V lattices for improved performance, (v) the lattice manufacturability and associated geometric errors, and (vi) clinical cases. Existing literature on the mechanical response of SEBM Ti-6Al-4V lattice structures is exhaustively evaluated for documentation quality using established theoretical models. This extensive data-set allows novel insights into the effect of lattice design on mechanical response that is not possible with the individual data; and provides a comprehensive database for those who are actively involved in patient-specific SEBM implant design. On this basis, outstanding challenges and research opportunities for SEBM Ti-6Al-4V lattices in the biomedical domain are identified and discussed.